Influence of Cr Substitution and Temperature on Hierarchical Phase Decomposition in the AlCoFeNi High Entropy Alloy. Issue 1 (December 2018) - Chaudhary, V.; Gwalani, B.; Soni, V.; Ramanujan, R.; Banerjee, R.
Abstract While the AlCoFeNi high entropy alloy exhibits a single ordered B2 phase at high temperature, both the substitution of ferromagnetic Co with antiferromagnetic Cr, and lower annealing temperatures lead to a tendency for this system to decompose into a two-phase mixture of ordered B2 and disordered BCC solid solution. The length scale of this decomposition is determined by the combination of composition and annealing temperature, as demonstrated in this investigation by comparing and contrasting AlCoFeNi with the AlCo0.5 Cr0.5 FeNi alloy. The resulting phase stability has been rationalized based on solution thermodynamic predictions. Additionally, it is shown that replacement of Co by Cr in the AlCoFeNi alloy resulted in a substantial reduction in saturation magnetization and increase in coercivity. The microhardness is also strongly influenced by the composition and the length scale of B2 + BCC decomposition in these high entropy alloys.